Pengaruh Penambahan Slot Terhadap Kinerja Antena WLAN - Charisma, Atik; Pratama, Reja; Rusiana Iskandar, Handoko; Haz, Fauzia (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2023)
One of the devices that plays an important role in the performance of Wireless LAN (WLAN) is the antenna. Microstrip antennas are generally used in high-frequency technology designs. Therefore it is suitable for increasing WLAN performance that works at the 2.4 GHz frequency. In this study, adding slots to the antenna to improve WLAN performance. The array antenna 2x1 is designed to work at the WLAN frequency of 2.4 GHz. The gain produced by this antenna is 3.8 dB which is very influential in strengthening the WLAN antenna signal.